Aminophylline affects glycemia control and increases anaerobic glycolysis in horses during incremental exercise - Ferraz, Guilherme C. [UNESP]; Teixeira Neto, Antônio Raphael [UNESP]; Lacerda-Neto, Jose C. [UNESP]; Pereira, Gener Tadeu [UNESP]; Queiroz-Neto, Antonio [UNESP] (Elsevier B.V., 2008)
A study was conducted on the effects of acute administration of aminophylline on physiological variables in purebred Arabian horses submitted to incremental exercise test. Twelve horses were submitted to two physical tests separated by a 10-day interval in a crossover study. These horses were divided into two groups: control (C, n = 12) and aminophylline (AM, n = 12). The drug at 10 mg/kg body weight or saline was given intravenously, 30 minutes before the incremental exercise test. The treadmill exercise test consisted of an initial warmup followed by gradually increasing physical exigency. Blood samples were assayed for lactic acid, glucose, and insulin. Maximal lactic acidemia was greater (P = .0238) in the AM group. Both V-2 and V-4 (velocities at which lactate concentrations were 2 and 4 mmol/ L, respectively) were reduced in the AM group by 15.85% (P = .0402) and 17.76% (P = .0 109), respectively. At rest as well as at 4 minutes, insulinemia was greater in the AM group (P = .0417 and .0393), Glycemia group at times 8 was statistically lower in the Al (P = .0138) and 10 minutes (P = .0432). Use of ammophylline in horses during incremental exercise does not seem to be beneficial, because this drug has a tendency to cause hypoglycemia and to increase dependence on anaerobic glucose metabolism.
Keywords: Horse; Exercise; aminophylline; Performance; Glucose; Insulin